Controllable spin diode based on a semiconductor quantum dot. (1st June 2022) - Bo, Rui; Xu, Qian; Qian, Yuan; Du, Juan; Zhang, Zhengzhong
Abstract: We theoretically propose an all-electrically controlled spin-current diode consisting of a quantum dot sandwiched between one normal electrode and one ferromagnetic electrode. By applying a spin bias V S across one electrode, the spin current distribution shows a rectification effect; that is, in the forward spin bias regime, a spin current can tunnel through the junction, while in the reverse bias regime, the current is tiny. Such asymmetry in the spin-current profile suggests diode-like behaviour with respect to the spin bias. Moreover, the polarity direction of this spin-current diode can be manipulated and reversed by adjusting the gate voltage, which is much more feasible than the approach with traditional charge-current diodes. The present device can be realized by current technologies and has potential applications in spintronics or quantum information processing.